High Flexible and Broad Antibacterial Nanodressing Induces Complete Skin Repair with Angiogenic and Follicle Regeneration. Issue 23 (6th May 2020) - Hu, Weikang; Wang, Zijian; Zha, Yao; Gu, Xiang; You, Wenjie; Xiao, Yu; Wang, Xinghuan; Zhang, Shengmin; Wang, Jianglin
Abstract: Complete skin reconstruction is a hierarchically physiological assembly involving epidermis, dermis, vasculature, innervation, hair follicles, and sweat glands. Despite various wound dressings having been developed for skin regeneration, few works refer to the complete skin regeneration, particularly lacking for vasculatures and hair follicles. Herein, an instructive wound dressing that integrates the antibacterial property of quaternized chitin and the mechanical strength and biological multifunction of silk fibroin through layer‐by‐layer electrostatic self‐assembly is designed and reported. The resultant dressings exhibit a nanofibrous structure ranging from 471.5 ± 212.1 to 756.9 ± 241.8 nm, suitable flexibility with tensile strength up to 4.47 ± 0.29 MPa, and broad‐spectrum antibacterial activity against Escherichia coli and Staphylococcus aureus . More interestingly, the current dressing system remarkably accelerates in vivo vascular reconstruction within 15 days, and the number of regenerated hair follicles reaches up to 22 ± 4 mm −2, which is comparable to the normal tissue (27 ± 2 mm −2 ). Those crucial functions might originate from the combination between quaternized chitin and silk fibroin and the hierarchical structure of electrospun nanofiber. This work establishes an easy but effective pathway to design a multifunctional wound dressing for the complete skin regeneration. Abstract : An instructive wound dressing (PQCSF: PCL/SF films self‐assembled with QC/SF) consisting of quaternized chitin (QC) and silk fibroin (SF) is fabricated through the layer‐by‐layer self‐assembly. The resultant PQCSF presents nanofibrous structure, suitable flexibility, good cytocompatibility, and broad‐spectrum antibacterial activity. In vivo evaluations further verify that this PQCSF can not only remarkably accelerate skin healing, but also effectively reconstruct vasculature and hair follicles of the regenerative skin.